Effective Supplier Reliability Introduction to Supply Chain & Supplier Quality Programs - Jayatilleka, Sarath (Proceedings. Annual Reliability and Maintainability Symposium, 2024)
The component with the lowest reliability may decide the overall system reliability. In so doing an outside supplier's part can bring down or raise the overall system's reliability. Consequently, supplier reliability management is paramount to overall product reliability. Supplier reliability is about educating them on customer's reliability requirements and customer accepting parts only after reliability requirement fulfilment is verified & validated (V&V) by suppliers. The concept of supplier reliability is often confused for "how dependable the supplier is." Somehow the concept of "supplier quality" is not confused due to its long history backed by Automotive Industry Action Groups (AIAG) and its IATF16949 standards. The main reason behind the improper understanding of supplier reliability is the frequently used non- scientific meaning of the term reliability. This social meaning is often meant for dependability that does not associate with time dimensions. This paper defines supplier reliability phrase to serve its primary purpose beyond supplier quality. When scientific statistical definition of reliability is introduced at the very first step of supplier communication, the gravity of supplier reliability can be elevated to a higher level from the beginning to the end during an execution of reliability program. During a new product development (NPD) program, suppliers become key stakeholders for NPD parts. Suppliers are solicited to take part in NPD activities to develop brand-new component/subsystems or to provide existing catalogue parts customizing to new customer requirements. Either way, when supplied parts are integrated into a new product, it requires proper integration testing and accelerated life testing (ALT) beyond the intended design life. This paper introduces the subject of supplier reliability, its elements, and its implementation across the reliability programs to supply chain and supplier quality organizations.